Homer's odyssey : a fearless feline tale, or, how I learned about love and life with a blind wonder cat - Cooper, Gwen, 1971- (Delacorte Press, 2009)
A pet rescue volunteer and literacy outreach coordinator describes her relationship with a three-pound blind cat whose daredevil character and affectionate personality saw the author through six moves, a burglary, and the healing of her broken heart.